Regulation of Transfer of Land Rights in Indonesian and Uzbekistan Civil Law: Philosophical Analysis of the Concept of Legal Certainty - Nurlani, Meirina; Baxadirovna, Bazarova Dildora (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The regulation of land rights transfer constitutes a vital instrument in realizing legal certainty and the protection of civil rights within society. Indonesia and Uzbekistan exhibit fundamental differences in their legal systems and traditions of land governance, which directly influence the manner in which legal certainty is established. Indonesia, through the Basic Agrarian Law of 1960 and Government Regulation Number 24 of 1997, adopts a negative land registration system with a positive tendency, while Uzbekistan, under the Land Code of 1998, declares land as state property administered under a national cadastre system emphasizing strict administrative registration.Purposes of the Research: The purpose of this study is to analyze and compare the regulation of land rights transfer in Indonesia and Uzbekistan by examining its implementation in light of legal certainty and civil law principles.Methods of the Research: This research employs a normative juridical method with a comparative legal and philosophical approach, particularly drawing upon the theory of legal certainty.Results Main Findings of the Research: The findings reveal that Indonesia continues to face weaknesses in formal legal certainty due to the non-absolute nature of its land registration system, which instead prioritizes the protection of subjective rights and substantive justice. Conversely, Uzbekistan enforces formal legal certainty through its cadastre system, yet tends to overlook substantive justice and the principle of consensualism. The novelty of this research lies in its philosophical analysis situating both countries within the comparative framework of legal certainty in civil law, thereby offering new discourse on the necessity of harmonizing legal certainty and substantive justice in the regulation of land rights transfer.